EXPLORING THE FACTORS AND STRATEGIES FOR ENSURING EDUCATIONAL STABILITY IN KWAZULU-NATAL: A FOCUS ON MITIGATING SCHOOL VIOLENCE AND PROMOTING A FAVORABLE LEARNING ENVIRONMENT - Ngogi Emmanuel Mahaye; Oluwatoyin Ayodele Ajani (International Journal of Innovative Technologies in Social Science, 2023)
Achieving educational objectives within the school system is contingent upon a conducive environment (Ajani, 2022). In the KwaZulu-Natal (KZN) province, the alarming rise in school violence has disrupted academic activities, sparking concerns among education stakeholders. Numerous incidents of violence, resulting in fatalities and property damage, have been well-documented (Mahaye et al., 2022). The recurring nature of these incidents has led to a lack of stability within schools, hindering effective teaching and learning. This study investigates the factors contributing to educational instability in KwaZulu-Natal, drawing from published literature and the authors' direct experience as education administrators. The research reveals that crime and violence are the primary causes of school instability, stemming from internal factors involving learners and staff and external influences from the local community. The study identifies multiple strategies to mitigate school violence, creating a secure and conducive educational environment. Additionally, it proposes measures to ensure school stability in the KwaZulu-Natal province, including moral guidance, heightened security protocols, the cultivation of emotional intelligence, instruction in African philosophy (Ubuntu), and improved teacher welfare packages.